Allegories of Divine Life - Grimes, John (Journal of Dharma, 1987)
As a vehicle for conveying the Life Divine, the allegorical is non-pareil. How enchanting, how lovely, how exquisite it is! An eternal relationshipexists between God and individuals. And yet, where is one to get the capacity to grasp the significance, the implications of this relationship?Will not one's understanding be coloured by one's worldliness? And still, since it is It Divine Play that is being conveyed, there ill the hope andpossibility that the capacity may come through.